2004
DOI: 10.1021/tx049960f
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism Is Required for the Expression of Ecstasy-Induced Cardiotoxicity in Vitro

Abstract: Cardiovascular complications associated with 3,4-methylenedioxymethamphetamine (MDMA, ecstasy) abuse have increasingly been reported. The indirect effect of MDMA mediated by a sustained high level of circulating biogenic amines may contribute to the cardiotoxic effects, but other factors, like the direct toxic effects of MDMA and its metabolites in cardiac cells, remain to be investigated. Thus, the objective of the present in vitro study was to evaluate the potential cardiotoxic effects of MDMA and its major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
55
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 36 publications
(62 reference statements)
6
55
0
1
Order By: Relevance
“…For instance, N-methylated metabolites of amphetamine-like drugs of abuse (e.g. 3,4-dihydroxymethamphetamine) were found to be important to understand the toxicological profile of "ecstasy", at a molecular level [54,55].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…For instance, N-methylated metabolites of amphetamine-like drugs of abuse (e.g. 3,4-dihydroxymethamphetamine) were found to be important to understand the toxicological profile of "ecstasy", at a molecular level [54,55].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…We have also previously demonstrated that the metabolism is important for MDMA-induced toxicity to peripheral organs. [18][19][20] The underlying mechanisms of MDMA and MDA-induced neurotoxicity, namely the toxic effects mediated by its metabolite(s), remain to be completely elucidated. Herein we present cyclic voltammetry studies that provide evidence for a correlation between the toxicity of MDMA and MDAmetabolites and their redox potential.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, since the reactive o-quinone intermediates are Michael acceptors, cellular damage can occur through alkylation of crucial cellular proteins and/or DNA. In the presence of GSH, o-quinone may be conjugated with GSH to form a glutathionyl adduct, 5-(glu- matsu et al, 1990;Carvalho et al, 2004c). This GSH conjugate remains redox-active, being readily oxidized to the quinone thioether, which, after the reductive addition of a second molecule of GSH, yields a 2,5-bis-glutathionyl conjugate (for detailed insights on MDMA metabolism, see Fig.…”
mentioning
confidence: 99%